Tourism development and its impacts to residents’ quality of life: case of Port Dickson / Norfarhana Abdullah, Nur Rasyiqah Abdul Rahman and Siti Haslinda Md Nor - Abdullah, Norfarhana; Abdul Rahman, Nur Rasyiqah; Md Nor, Siti Haslinda (2015)
In this section, we provide an explanation o f and support for the research questions. Later on, the study objective is defined and the theoretical basis for the study is explained. Three objectives with associated hypotheses are presented and a description of the structure model used in the study is presented next. Then a discussion of the contributions of the study is given.